Numerical simulation of gap effect in supersonic flows - Song Mo; Haiming Huang; Guo Huang; Xiaoliang Xu; Zimao Zhang (Theoretical and Applied Mechanics Letters, 2014)
The gap effect is a key factor in the design of the heat sealing in supersonic vehicles subjected to an aerodynamic heat load. Built on S-A turbulence model and Roe discrete format, the aerodynamic environment around a gap on the surface of a supersonic aircraft was simulated by the finite volume method. As the presented results indicate, the gap effect depends not only on the attack angle, but also on the Mach number.